Defying planned obsolescence: Paradigm change for macro level sustainability of supply chain management systems - (:unkn) unknown (Computers and Industrial Engineering, 2014)
Planned obsolescence with products designed to fail has become the main drive of modern consumption based economies based on the paradigm promoting growth as an essential activity for survival. Engineers face nowadays a dilemma when concerning sustainability in problem solving during engineering applications. They are stuck between the growth, or survival of businesses through planned obsolescence and the sustainability issues. For sustainability, majority suggests ways such as optimizing product life (meaning a delayed planned obsolescence), recycling through waste collection and reprocessing of the resultant products (reverse logistics), more efficient ways in supply-chain management systems etc. This is a paradigm paralysis and a paradigm shift is needed for really sustainable world and macro level sustainability of supply-chain management systems. This paper analyzes the real root cause of the problem and shows how the unlimited growth paradigm promoted by the modern money creation called Debt Based Monetary System. It then suggests a paradigm shift towards defying planned obsolescence for macro-sustainability of supply-chain management systems.
Keywords: Industrial design; Planned obsolescence; Reverse logistics; Sustainable supply chain management systems